Thyroid Dysfunction And Anti-Thyroid Peroxidase Antibody In Patients With Vitiligo - Singh, Suman (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Background Vitiligo is an acquired depigmenting disorder due to destruction of melanocytes. An increased prevalence of autoimmune thyroid disease has been described in these patients. The aim of this study is to compare the frequency of anti-thyroid peroxidase antibody (anti-TPO) and to assess the prevalence of thyroid dysfunction in vitiligo patients with healthy subjects. Methods Sera from 118 patients of vitiligo and 50 control subjects without any clinical evidence for thyroid dysfunction were assayed for thyroid profile (free T3, Free T4 and TSH) and anti-TPO antibodies. Result Our study concludes that about 12.7% vitiligo patients have associated hypothyroidism. Anti-TPO was detected in 21 (17.8%) of patients while none of the control was positive; the difference was significant with p value < 0.000. Conclusion According to our study thyroid dysfunction particularly towards hypothyroidism and anti-TPO was shown to be significantly more common in vitiligo patients compared with control group. As this antibody is sensitive and specific marker of autoimmune thyroid disorders, we recommend thyroid function evaluation and thyroid antibodies detection in these patients.